Comparison of artificial diets for rearing Corcyra cephalonica (Stainton, 1865) (Lep., Pyralidae) for Trichogramma mass production - BERNARDI,E. B. (2000)
The objective of this research was, based on biological studies, to determine and adequate diet for rearing Corcyra cephalonica (Stainton, 1865) in the laboratory so as to permit the rearing of this factitious host for Trichogramma mass production. The research was conducted at 25 ± 1ºC, RH 60 ± 10% and photophase of 14 hours. Six artificial diets were compared: a) whole wheat flour (48.5%), ground rice (48.5%) and sugar (3%); b) ground rice (97%) and sugar (3%); c) whole wheat flour (48.5%), rice flour (48.5%) an sugar (3%); d) whole wheat flour (97%) and yeast (3%); e) wheat germ (97%) and yeast (3%); f) rice bran (94%), sugar (3%) and yeast (3%); f) rice bran (94%), sugar (3%) and yeast (3%). All of the diets studied permitted the development of C. cephalonica although the diets with wheat germ and yeast and that consisting of rice bran, sugar and yeast proved to be the most adequate for rearing the moth. These diets reduced the total (egg-adult) cycle, shortened the egg laying period, and produced heavier adults. Studies on the fertility life tables showed that higher net reproduction rates (Ro) and finite ratio of increase (lambda) were obtained from adults reared on these diets.